REAKSI INVESTOR DALAM PASAR MODAL TERHADAP UNDANG-UNDANG TAX AMNESTY (EVENT STUDY PADA PERUSAHAAN YANG TERDAFTAR DALAM IDX 30 DI BURSA EFEK INDONESIA) - Nida Nur Diyanah; Budi Susetyo; Yanti Puji Astutie (Multiplier: Jurnal Magister Manajemen, 2017)
This research is aimed to know the differences of abnormal return, stock trade volume, and stock trade frequency in before and after the existance of Tax Amnesty Laws. Kind of this research was quantitative research by using secondary data that was gained from company's annual report. Population used in this research was enrolled companies in IDX 30 in Indonesia Stock Exchange that the total was 30 companies. In sample taking technique, the reseacher used purposive sampling with enrolled companies' criterias in IDX 30 periodes March 2017 - April 2017. Tecnique of analyzing data that was used is Wilcoxon Signed Rank Test. The result of this research shows that there are no differences of abnormal return in before and after the existance of Tax Amnesty Laws with score Asymp.Sig 2 Tailed 0,398. In hypothesis 2, there are the differences of stock trade volume in before and after the existance of Tax Amnesty Laws with score Asymp.Sig 2 Tailed 0,000. Then in hypothesis 2, there are the differences of stock trade frequency in before and after the existance of Tax Amnesty Laws with score Asymp.Sig 2 Tailed 0,000. Â Keywords: abnormal return, stock trade volume, stock trade frequency, and Tax Amnesty.